1998
DOI: 10.1001/archneur.55.11.1425
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Research Designs for Emerging Treatments for Alzheimer Disease

Abstract: The design of clinical trials must evolve as new therapies become available. The demonstrated efficacy and clinical use of donepezil and vitamin E for Alzheimer disease (AD) has shifted the options for AD research design. There is now a compelling case for alternatives to trials that include a treatment arm with no active therapy (ie, a placebo control). With an existing therapy, such as donepezil or vitamin E, new drugs that are clearly superior to those drugs should be sought. Combination therapy is a likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…psychotic behavior or insomnia) the question is not whether the new drug is more effective than placebo but rather what are its advantages (and disadvantages) versus the best available drug in the market, or the most popular one, which should be used for comparison. Although this issue is not unique to studies in demented people, it is particularly relevant because of the vulnerability of demented individuals [11][12][13][14][15].…”
Section: Study Aimsmentioning
confidence: 99%
“…psychotic behavior or insomnia) the question is not whether the new drug is more effective than placebo but rather what are its advantages (and disadvantages) versus the best available drug in the market, or the most popular one, which should be used for comparison. Although this issue is not unique to studies in demented people, it is particularly relevant because of the vulnerability of demented individuals [11][12][13][14][15].…”
Section: Study Aimsmentioning
confidence: 99%
“…Combinations of two of these agents have already been tested in a phase III clinical trial, and showed a trend toward unexpected antagonistic effects [25]. The possibility of developing a 'cocktail' of neuroprotective agents for AD has gained wide attention among researchers and the lay public [35][36][37].…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…It has been suggested that the lack of adverse effects of donepezil refutes analogies based on the clinical utility of looking for drugs with lesser toxicity. 1 Unfortunately, donepezil, though far less toxic than tacrine, still causes significant adverse effects in some patients (in the 24-week pivotal trial, 16% of the subjects receiving 10 mg/d of donepezil discontinued the trial because of adverse events). 4 All cholinesterase inhibitors, both approved and in late stages of development, cause significant cholinergic adverse effects in some patients.…”
Section: See Also Pages 1420 and 1425mentioning
confidence: 99%
“…The justifications for using placebos in depression studies are (1) significant efficacy with current drugs may make it statistically difficult to prove superiority of a new drug in relation to an existing drug; (2) new drugs of equivalent efficacy with fewer adverse effects are still needed; (3) new drugs are needed as second-line drugs; (4) new drugs may provide a better understanding of different features of neurobiology of the disease; (5) high rates of placebo response for existing drugs could lead to falsely concluding therapeutic equivalency between a new drug and an old one; and (6) there may be greater difficulty discerning adverse effects of a new drug against an active control. 1 It has been suggested that, even in diseases with significant placebo response rates, a new drug is only…”
mentioning
confidence: 99%